Aporte al conocimiento de ciclos de materia orgánica (MO) en formaciones boscosas de la llanura de inundación del Río Paraná: Area PNPD - Zamboni, Lisandra Pamela (2004)
A study was made to know the organic matter (OM) cycling in tree representative forest of Paraná River Floodplain. It was carried out in Pre-Delta National Park (Entre Ríos, Argentina) during the 2001/2 period. The time-course of the litter fall for different organs of the trees was followed, also litter decomposition rates were followed. The mean total production of litter in Salix humboldtiana forest was 475 gr/m2/year; 464 gr/m2/year for Tessaria integrifolia and 245 gr/m2/year for Albizia inundata. The temporal pattern showed maximum fall values during winter-spring period (July-January). S. humboldtiana shows lower litter decomposition rates (k) and higher permanence time; on the other hand, A. inundata shows higher decomposition rate and consequently lower permanence as forest litter.